Antenatal Anemia: Predictor of Poor Maternal and Perinatal Outcome - Saba Pario, Ghazala Nasim Pasha, Sadia Suboohi Sadiq, Zahra Salahuddin, Hafsa Abdul Malik, Shahnaz Hassan Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the impact of antenatal anemia on maternal and perinatal outcome. Design of the study: Prospective Cohort study Place of Study: was conducted at antenatal clinic of Creek General Hospital, United Medical and Dental College, Karachi, Pakistan. Methodology: One hundred and thirty-five singleton anemic pregnant women who satisfied the inclusion criteria were included in the study. Enrolled patients were analyzed in detail, sociodemographic and obstetric characteristics recorded and followed till delivery after their informed consent. Haemoglobin estimation was done at first visit & anaemia was graded according to WHO criteria and statistical analysis were done. Results: The study population included 135 antenatal anemic women. Mean ± SD of maternal age was 25.8±5.12 years. Mild anemia was found in 31.1%, moderate in 59.2% and 9.6% women were diagnosed with severe anemia. Anemia was diagnosed in 1.5% of antenatal women in 1st trimester, 54.8% in 2nd trimester and 43.7% in 3rd trimester. Majority of patients were booked (87.4%), out of them 25.9% were diagnosed with mild anemia, 55.6% with moderate and 5.9% were severely anemic, while 12.59% were non-booked of those 5.2% were diagnosed with mild, 3.7 % with moderate and severe anemia each (p-value=0.003%). Maternal complications in antenatal and postnatal period included Preterm labour (13.33%), Pregnancy induced hypertension/ Pre-eclampsia (8.88%), Gestational diabetes mellitus (7.40%), oligohydramnios (11.85%) , antepartum hemorrhage (5.92%) and Postpartum hemorrhage (5.18%). 50.37% of pregnant women delivered vaginally while in 49.62 % abdominal delivery was conducted (Emergency-37 %, Elective -12.6%). Regarding Neonatal outcomes, Low Birth weight was found in 80% of cases which was highly significant, 20.7% were delivered by mildly anemic, 52.6% by moderately and 6.7% by severely anemic mothers (p value- 0.009). NICU admission within the first week of birth was needed in 47.40%, Still Birth (0.74%), Low APGAR scores (20.74%) and unfortunately two Neonatal Deaths occurred as well (1.48%). Conclusion: Antenatal anemia is still a prevalent public health issue in developing countries. Provided that anemia is a straightforward predictor of poor maternal and fetal outcome, intensive prophylactic strategies to be implemented for timely diagnosis and management. The authorities should play their active role in refining policies to remediate the principal risk factors, provision of basic health care, reinforce proper antenatal care, maintain regular availability of iron and supplements for correction of anemia and other nutritional deficiencies.